Quality and safety of small scale beef products in East and Central Africa. - Kurwijila, Lusato R.; Birungi, Rosemirta; Makokha, S.; Musahara, H.; Otika, L.; Adissu, A.; Omore, Amos O. (Association for Strengthening Agricultural Research in Eastern and Central Africa, 2011)
The annual per capita meat demand in Africa will reach 22kg by 2050. This exponential increase will necessitate a corresponding rise in demand for livestock. It suggests similar increases throughout the developing world. In Eastern and Central Africa (ECA), the growing demand for quality meat products is driving opportunities for value addition. The ECA countries need to put in place measures to exploit this opportunity. However, significant technical and institutional barriers continue to limit the small-scale meat producers and market agents from exploiting these opportunities. This brochure provides the beef producers, market agents, processors and retailers information on quality and safety perspectives of consumers, niche markets and, regulatory and policy institutions. The information could enhance the adoption of addition innovations in the meat sub-sectors in ECA.